Perencanaan Peningkatan Jalan Kawasan Merancang Kecamatan Gunung Tabur Kabupaten Berau Provinsi Kalimantan Timur - Djufri; Rahmatullah (CV. ALIM'SPUBLISHING, 2023)
This community service aims to carry out location mapping in planning activities to obtain an appropriate and comprehensive design for activities to increase the capacity and quality of roads in the Design area, Gunung Tibar District, Berau Regency, East Kalimantan Province. The method used was photography and direct measurements as well as assessment by a team appointed by the Berau Regency Government, both from the condition of the road to measuring the distance of the road whose quality would be improved at a 1,300m location stretching from the Jalan Poros Tanjung Batu area to the end of the Persimpangan Jalan Pertanian.